Cell-Free DNA, High-Mobility Group Box-1, and Procalcitonin Concentrations in Dogs With Gastric Dilatation–Volvulus Syndrome - Troia, Roberta; Giunti, Massimo; Calipa, Stefano; Goggs, Robert (Frontiers in Veterinary Science, 2018)
Canine gastric dilatation-volvulus (GDV) is a life-threatening disease characterized by extensive tissue ischemia, tissue hypoperfusion and systemic inflammation. Biomarkers that better reflect the severity of gastric necrosis and systemic inflammation would aid clinicians in the management of these patients. This study aimed to investigate the prognostic significance of cell-free DNA (cfDNA), high-mobility group box-1 (HMGB1) and procalcitonin (PCT) in dogs with GDV. Concentrations of cfDNA, HMGB1 and PCT were measured in citrated plasma samples collected from 29 dogs with GDV at hospital admission. Additional data collected included baseline lactate concentrations, APPLEfast score, evidence of gastric necrosis, occurrence of postoperative complications and outcome. Twenty-four healthy dogs were sampled as controls. Continuous variables between groups were compared with the Mann-Whitney U and correlations between continuous variables were assessed by calculation of Spearman's correlation coefficient. Alpha was set at 0.05. Dogs with GDV had significantly greater concentrations of cfDNA, HMGB1 and PCT compared to controls (P=0.0009, P=0.004 and P=0.009, respectively). Procalcitonin concentrations were significantly higher in non-survivors compared to survivors (P=0.008). Dogs with gastric necrosis had significantly greater lactate concentrations compared to dogs without gastric necrosis (P=0.0005). The APPLEfast score was not prognostic. Lactate and PCT concentrations were moderately, positively correlated (rs 0.51, P=0.0005). Concentrations of the inflammatory biomarkers cfDNA, HMGB1 and PCT are increased in canine GDV. Only lactate and PCT concentrations were prognostic in this population of GDV dogs, and were predictive of the presence of gastric necrosis and of non-survival to hospital discharge, respectively.